Oil : an overview of the petroleum industry - Grace, Robert (Gulf Pub. Co., 2007)
Now in its sixth edition, this guide to the oil industry, written in non-technical language, is a must-read for anyone involved in or curious about the oil industry. Engineers, executives, managers and laypersons will all find this to be a valuable, entertaining and informative guide that presents a practical study of the operations involved in oil exploration, drilling and production. Since the book's original publication in 1958, this handy volume has taught thousands about this constantly evolving industry that is so important for our everyday energy needs.